Refinement process and mechanisms of tungsten powder by high energy ball milling. (September 2017) - Liang, Y.X.; Wu, Z.M.; Fu, E.G.; Du, J.L.; Wang, P.P.; Zhao, Y.B.; Qiu, Y.H.; Hu, Z.Y.
Abstract: The grain refinement process and mechanisms of tungsten powder during ball milling are explored based on different ball milling time. From the results of scanning electron microscopy (SEM), the model for ball milling process is proposed to include four stages: welding stage, squeezing stage, fracturing stage and dynamic balance stage. Microstructure of tungsten powder examined by transmission electron microscopy (TEM) shows that the tungsten powder ball milled for 50 h has polycrystalline grains and most of them have long strip structure with high angle grain boundaries. Nanocrystalline tungsten powder with minimum grain size of 5 nm was obtained in the final stage of ball milling. Highlights: Provide an insight into interactions between tungsten powder and surrounding in a vial during high energy ball milling. Reveal morphology and microstructure of tungsten powder in different stages during the whole ball milling process. Illustrate the mechanisms of tungsten powder in different stages by high energy ball milling. Nanocrystalline tungsten powder with grain size smaller than 20 nm was successfully fabricated and the powder with minimum grain size of 5 nm was obtained in final step of ball milling.